2011
DOI: 10.1371/journal.pone.0027177
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Transgenic DNA from Orally Administered Bt MON810 Maize and Effects on Immune Response and Growth in Pigs

Abstract: We assessed the effect of short-term feeding of genetically modified (GM: Bt MON810) maize on immune responses and growth in weanling pigs and determined the fate of the transgenic DNA and protein in-vivo. Pigs were fed a diet containing 38.9% GM or non-GM isogenic parent line maize for 31 days. We observed that IL-12 and IFNγ production from mitogenic stimulated peripheral blood mononuclear cells decreased (P<0.10) following 31 days of GM maize exposure. While Cry1Ab-specific IgG and IgA were not detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 39 publications
(57 reference statements)
10
65
2
Order By: Relevance
“…Although regulatory agencies issued precise frameworks for adoption of transgenic crops, concerns about the safety of transgenic products still remain (Walsh et al, 2011). Among the most discussable aspects of transgenic crops are toxicity and allergencity (Dona and Arvanitoyannis, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although regulatory agencies issued precise frameworks for adoption of transgenic crops, concerns about the safety of transgenic products still remain (Walsh et al, 2011). Among the most discussable aspects of transgenic crops are toxicity and allergencity (Dona and Arvanitoyannis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The fate of recombinant feed and food DNA in the GIT of animals and its potential absorption and transfer to other tissues was reported by many researchers. The digestive fate of recombinant DNA and protein from transgenic plants has been studied in rats, fish, cattle, sheep, poultry and pigs (El-Sanhoty et al, 2006;Sharma et al, 2006;Walsh et al, 2011;Swiatkiewicz et al, 2014). In the studies using transgenic crops (maize, rice, potato, soyabean) no adverse effects on the nutrition of rats, chickens, broiler chickens, catfish, dairy cattle, bulls and sheep have been shown (Duggan et al, 2003;He et al, 2009;Snell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that Bt toxin has immunogenic properties, whose effects have been identified in mice and pigs (Andreassen et al, 2014;Walsh et al, 2011). Pigs fed a GMO diet had a larger uterus and presented severe stomach inflammation compared with pigs fed a comparable non-GMO diet (Carman et al, 2013).…”
Section: B) Food That Contains An Ingredient or An Additive Derived Fmentioning
confidence: 99%
“…Results of Cry1Ab toxin concentrations determined in porcine tissue samples were available from pig feeding studies (WALSH et al, 2011BUZOIANU et al, 2012). Organ samples were heart, kidney, spleen, liver, muscle, lymph node, brain, and serum of pigs fed with GM MON 810 (PR34N44) and non-GM isogenic maize (PR34N43).…”
Section: Matrix Effectmentioning
confidence: 99%
“…To study possible occurrence of Cry1Ab in porcine tissues, feeding studies with PR34N44 Bt-maize were performed (WALSH et al, 2011;BUZOIANU et al, 2012;WALSH et al, 2012), and results indicated that appearance or detection success of Bt toxin in different tissues is not uniform. Cry1Ab was positively detected in stomach content and digesta samples, but fell below the LOD for other tissues.…”
mentioning
confidence: 99%